Analysis of Cost Structure Allocation Against Financial Feasibility in the Bumi Mutiara Industry in Palu City - Adam, Adinda Elfara Rizki Adam Fara (Universitas Tadulako, 2025)
Ground coffee, as a processed product of coffee beans, stands as an agricultural commodity with significant market prospects, driven by the proliferation of cafes, coffee stalls, and modern coffee beverage trends. The sales potential of this processed coffee offers attractive profitability, fostering the growth of the coffee processing sector, one example being the Bumi Mutiara Industry. This research focuses on evaluating the financial feasibility of the Bumi Mutiara Ground Coffee Industry in Palu City. The aspects reviewed include capital structure, financing composition, production techniques, raw material procurement strategy, and product marketing. The financial analysis results indicate a very promising outlook for this venture. The calculated Net Present Value (NPV) is a positive Rp187,500,267.00. The Internal Rate of Return (IRR) of 24% significantly exceeds the benchmark interest rate (24% > 12%). Furthermore, the Net Benefit-Cost Ratio (Net B/C) is 1.41, which is greater than 1. Concurrently, the Payback Period (PP) for the business is recorded at 3 years and 3 months. Based on all these financial feasibility indicators, it is concluded that the Bumi Mutiara Ground Coffee Industry in Palu City is financially viable for both continuation and future development.